Influência do processamento no teor de compostos fenólicos e na avaliação sensorial de geléia de jabuticaba (Myrciaria jaboticaba Vell. Berg) - Laila Carline Goncalves Rezende (2011)
The jaboticaba (Myrciaria jaboticaba Vell. Berg) is a native brazilian fruit that has a peel with a large amount of phenolic compounds, to which various beneficial health properties have been attributed. Due to the high perishability of the fruit, the processed products derived from it, like the jelly, are interesting because they have higher durability and possess the potentially beneficial substances extracted from the peel. The aim of this study was to compare the physicochemical and sensory properties of two jellies produced from an aqueous jaboticaba extract obtained from fruits that were processed for 15 or 60 seconds in a mechanical processor. The extract was sweetened with 50% sucrose and subjected to heat treatment. The content of total phenolic substances varied from 312,45 to 325,33 mg.100 g-1, tannins varied from 226,26 a 252,91 mg.100 g-1 and presented a significant difference, being higher for the jelly processed for 60 seconds. The monomeric anthocyanin content ranged from 22,43 to 23,92 mg.100 g-1 and the contribution of polymeric anthocyanins to the color varied from 44,35 to 46,67%. The acidity was high and the total soluble solids content was below the level recommended by legislation. All sensory attributes evaluated in the jellies had notes in the region of acceptance in the scale used and both jellies showed positive purchase intents. The jellies of this work are an option for the intake of phenolic compounds because they are rich in this compounds and showed good acceptability by the panelists, especially the jelly processed for 60 seconds , which is higher in total phenolic compounds and tannins.